Localization of estrogen receptor-alpha in human and rabbit skeletal tissues. - Kusec, V; Virdi, A; Prince, R; Triffitt, J (1998)
Estrogen is essential for the development and maintenance of optimal bone mass in women and men, and acts through activation of estrogen receptors (ER). We have examined the pathways of estrogen action on the skeleton by seeking to localize the "classical" estrogen receptor, ER alpha, to particular cells to test the hypotheses that 1) estrogen directly influences growth plate chondrocytes; and 2) estrogen has a principal action on bone tissue via osteoblasts. ER alpha messenger ribonucleic acid (mRNA) was localized by in situ hybridization in human specimens from five males (11-15 yr old), two females (9 and 11 yr old), and three growing rabbits. In all of the human material examined, ER alpha mRNA was consistently identified in chondrocytes. In all of the rabbit tissue studied, ER alpha mRNA was localized in chondrocytes of the growth plate and the subarticular epiphyseal growth center. ER alpha mRNA signals were readily observed in both active osteoblasts and lining cells on trabecular surfaces of all samples. No clear evidence of positive staining was detectable in osteoclasts or osteocytes in either species. The distribution of ER alpha mRNA coincided with immunolocalization of the ER protein in the human specimens. These data suggest a direct action of estrogen on growth plate chondrocytes that may affect longitudinal growth and subsequent fusion of the growth plate and also on osteoblasts to affect bone formation at trabecular sites.